Handbook of SCADA/control systems security - Radvanovsky, Robert (CRC Press, 2013)
The availability and security of many services we rely upon-including water treatment, electricity, healthcare, transportation, and financial transactions-are routinely put at risk by cyber threats. The Handbook of SCADA/Control Systems Security is a fundamental outline of security concepts, methodologies, and relevant information pertaining to the supervisory control and data acquisition (SCADA) systems and technology that quietly operate in the background of critical utility and industrial facilities worldwide. Divided into five sections, the book examines topics comprising functions within.